Satisfaction with primary health care services among patients with chronic diseases: a qualitative study - Alshagrawi, Salah; Albaqami, Naif Mohammed (Frontiers in Medicine, 2026)
BackgroundPatients with chronic illnesses exhibit elevated healthcare utilization and costs, increased prevalence of depression, and impaired functional capacity. Most healthcare systems rely on primary care physicians (PCPs) to manage the treatment of patients with chronic diseases. Studies have demonstrated that patients who report high-quality care have higher treatment adherence rates, increased self-management skills, and a positive, ongoing relationship with their PCPs. This study aimed to explore the factors influencing satisfaction among patients with chronic diseases receiving primary health care (PHC) in Saudi Arabia.MethodsA qualitative technique was employed to thoroughly comprehend the intricacies of participant experiences. Online semi-structured interviews were carried out with individuals diagnosed with one or more chronic diseases and who have visited PHC. The thematic analysis framework described by Braun and Clarke was employed to code and thematically assess the data by using NVivo software. The identification of themes and sub-themes resulted in the establishment of an initial coding framework.ResultsData saturation was attained following the interviews of 46 patients (n = 46). The majority of participants were women, and 66% were over 50. 70% were married, 65% had college degrees, and 17% earned less than 5,000 SAR monthly. Nearly half had three or more chronic illnesses. Our thematic analysis revealed 5 themes relevant to the factors that influence the level of satisfaction among patients with chronic diseases concerning the services provided by their PCP: access to care; respect for patient-centered values, preferences, and expressed needs; coordination and integration of care; information, communication, and education; emotional and mental support; and transition and continuity.ConclusionOur study found that dissatisfaction with accessing care remains for particularly vulnerable populations, such as the elderly, residents of remote areas, and individuals with low literacy skills. Insufficient interaction, inadequate privacy, and exclusion from the decision-making process were also significant concerns expressed by our participants, who emphasized the need for a sustained, long-term connection that fosters positive rapport, acknowledges customer competence, ensures effective communication, and addresses consumers’ mental health. Thus, it is necessary to implement fundamental modifications at various levels, including medical education, health systems, and tailored regulations, to create a general environment that promotes the establishment of an effective doctor-patient relationship.